2021
DOI: 10.1088/1361-6560/abdc30
|View full text |Cite
|
Sign up to set email alerts
|

IPEM topical report: guidance on the use of MRI for external beam radiotherapy treatment planning *

Abstract: This document gives guidance for multidisciplinary teams within institutions setting up and using an MRI-guided radiotherapy (RT) treatment planning service. It has been written by a multidisciplinary working group from the Institute of Physics and Engineering in Medicine (IPEM). Guidance has come from the experience of the institutions represented in the IPEM working group, in consultation with other institutions, and where appropriate references are given for any relevant legislation, other guidance document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…17 Recent recommendations that a three-dimensional (3D) isotropic T2-weighted axial acquisition is justified for prostate radiation therapy planning have also been published. 19,20 We verified that an isotropic T2 SPACE (Sampling Perfection with Application optimised Contrasts using different flip angle Evolution) sequence could produce a 3D prostate image of satisfactory quality for clinical use by our GU radiation oncologists (ROs). We found a 0.9 mm isotropic scan provided optimal image quality for multiplane RT planning (Fig.…”
Section: Introductionmentioning
confidence: 70%
“…17 Recent recommendations that a three-dimensional (3D) isotropic T2-weighted axial acquisition is justified for prostate radiation therapy planning have also been published. 19,20 We verified that an isotropic T2 SPACE (Sampling Perfection with Application optimised Contrasts using different flip angle Evolution) sequence could produce a 3D prostate image of satisfactory quality for clinical use by our GU radiation oncologists (ROs). We found a 0.9 mm isotropic scan provided optimal image quality for multiplane RT planning (Fig.…”
Section: Introductionmentioning
confidence: 70%
“…Some of the aspects that vary, such as equipment required, MR sequence optimisation, commissioning and QA, and safety features could benefit from guidance from professional bodies. It is known that IPEM has published guidance (Speight et al 2021) and AAPM are working on such guidance, as well as the Nederlandse Commissie voor Stralingsdosimetrie (NCS) who are producing guidelines specifically on MRI QA for RT. Guidance is available for commissioning and QA of MRI scanners for diagnostic purposes (Jackson et al 2010, ACR 2015, McRobbie and Semple 2017, but the requirements for MR for EBRT are different from radiology and hence the QA requirements are different.…”
Section: Discussionmentioning
confidence: 99%
“…The IPEM working party has addressed some of the issues identified in this work in the form of guidelines for the safe implementation for MR for EBRT (Speight et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the UK, only 6% of radiotherapy patient treatments used MRI guidance in 2018 and only two radiotherapy centres had dedicated radiotherapy MRI equipment [4]. However, the rationale for the increased use of MRI simulation in radiotherapy is building, through increased evidence of the benefit to patients [5e8], the development of new techniques, such as MRI-only planning [9e11], and recommendations from national bodies on commissioning and use [12,13]. A recent Institute of Physics and Engineering in Medicine (IPEM) international survey of MRI use in radiotherapy showed that a significant number of centres are planning to implement MRI simulation in the next 5 years [3].…”
mentioning
confidence: 99%